2017
DOI: 10.1371/journal.pone.0181949
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of beef and pork materials in meat products by duplex droplet digital PCR

Abstract: Meat products often consist of meat from multiple animal species, and inaccurate food product adulteration and mislabeling can negatively affect consumers. Therefore, a cost-effective and reliable method for identification and quantification of animal species in meat products is required. In this study, we developed a duplex droplet digital PCR (dddPCR) detection and quantification system to simultaneously identify and quantify the source of meat in samples containing a mixture of beef (Bos taurus) and pork (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 23 publications
2
35
1
Order By: Relevance
“…These results support previous findings, as PCI method has been used in many DNA isolation studies in this field [3,7,12,15]. Compared to PCI method, isolation kit method showed relatively low DNA yield, albeit having good DNA quality.…”
Section: Results and Discussion Conventional Pci Methods Showed Reliablsupporting
confidence: 90%
“…These results support previous findings, as PCI method has been used in many DNA isolation studies in this field [3,7,12,15]. Compared to PCI method, isolation kit method showed relatively low DNA yield, albeit having good DNA quality.…”
Section: Results and Discussion Conventional Pci Methods Showed Reliablsupporting
confidence: 90%
“…It is important to note that Poland is one of the leading European exporters of game: in 2014, 3363 tonnes of wild boar meat was exported, representing over 30% of all exported game meat [23]. It was also found that meat products are often produced by combining meat from different animal species, which significantly increases the risk of infection [1,6].…”
Section: Discussionmentioning
confidence: 99%
“…Rising consumer demand underscores the need for the development of more swift and reliable methods to identify species in food commodities such as detecting pork in food. On this note, instead of protein, a DNA analysis would be preferable to identify species due to the nature of protein being easily denaturised while processing [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%